The Effect of Dekokta Jamu Cekok on Short Term Memory of White Rats (Rattus norvegicus L.) Male Wistar Strain - Nelli Jaliyanti; Puji Astuti; Hadi Kurniawan; Ery Hermawati; Alex Alex (Biology, Medicine, & Natural Product Chemistry, 2026)
The rising prevalence of dementia in Indonesia has resulted in a decline in memory and cognitive abilities. This condition is believed to be linked to oxidative stress caused by an imbalance between free radicals and antioxidants. Jamu cekok, a traditional herbal remedy composed of rhizomes such as Kaempferia galanga, Zingiber officinale, Curcuma longa L., and Curcuma xanthorrhiza, is known for its antioxidant properties. These antioxidants have the potential to neutralize free radicals, thereby helping to prevent degenerative diseases like dementia and Alzheimer’s, which are associated with short-term memory impairment. This study aimed to evaluate the effects of jamu cekok decoction on the short-term memory of male Wistar rats (Rattus norvegicus L.). A laboratory-based experimental study with a post-test-only control group design was conducted. Male Wistar rats were divided into three treatment groups receiving jamu cekok doses of 100, 200 and 400 mg/kg BW, and a negative control group was included. Short-term memory was assessed using the Y-maze test. The highest Y-maze alternation percentage of 65.12% was observed in the treatment group receiving a dose of 400 mg/kg BW. However, statistical analysis using the Kruskal-Wallis test showed no significant difference in Y-maze alternation percentages among the groups receiving jamu cekok (p = 0.626). The findings indicate that jamu cekok decoction did not have a significant effect on the short-term memory of male Wistar rats. Further studies with larger sample sizes and alternative assessment methods are recommended to explore its potential cognitive benefits.